2021
DOI: 10.1186/s12987-021-00246-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of cerebrospinal fluid velocity measurement in type I Chiari malformation: repeatability, reproducibility, and agreement using 2D phase contrast and 4D flow MRI

Abstract: Background Phase contrast magnetic resonance imaging, PC MRI, is a valuable tool allowing for non-invasive quantification of CSF dynamics, but has lacked adoption in clinical practice for Chiari malformation diagnostics. To improve these diagnostic practices, a better understanding of PC MRI based measurement agreement, repeatability, and reproducibility of CSF dynamics is needed. Methods An anatomically realistic in vitro subject specific model of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…These techniques include magnetic resonance imaging (MRI), two-photon imaging, computer-assisted cisternography (CT cisternography), and scanning electron microscopy (SEM). Moreover, phase contrast techniques are also widely used in the CSF study ( 63 ).…”
Section: Imaging Techniques To Visualize the Csf Circulationmentioning
confidence: 99%
“…These techniques include magnetic resonance imaging (MRI), two-photon imaging, computer-assisted cisternography (CT cisternography), and scanning electron microscopy (SEM). Moreover, phase contrast techniques are also widely used in the CSF study ( 63 ).…”
Section: Imaging Techniques To Visualize the Csf Circulationmentioning
confidence: 99%
“…Williams et al performed 4D flow MRI (3T; spatial resolution, 1.5 × 1.5 × 1.5 mm 3 ; and VENC, 15 cm/s) on an in vitro model of Chiari malformation and compared the CSF velocities with those obtained by 2D cine PC MRI, and reported that the CSF velocities showed good accuracy in each case. 82 Currently, it is difficult to accurately reproduce the geometry of the SSS in CFD and in vitro models due to its detailed and complex structure, and these are not considered to be the ideal true value for human 4D flow MRI measurements for SSS. Therefore, at this time, the measurement accuracy of 4D flow MRI for the human SSS should be examined using existing 2D cine PC MR, whose accuracy has been confirmed.…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%
“…34 On the other hand, in an in vitro experiment using a subject-specific CSF flow model of a Chiari malformation patient, 4D flow MRI was performed three times with five different devices at five centers, and the test-retest repeatability was good, but inter-scanner reproducibility was poor. 82 The reason raised in that paper was that the imaging parameters could not be sufficiently matched.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…A benefit of 4D flow MRI is that it is not influenced by the placement of the acquisition plane and, thus, enables efficient provision of complex CSF movements in all three spatial directions. Taking advantage of these benefits, several studies have reported on 4D flow MRI measurements of the CSF flow pattern over the past decade 11–16 …”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of these benefits, several studies have reported on 4D flow MRI measurements of the CSF flow pattern over the past decade. [11][12][13][14][15][16] Flow velocity measurement using PC-MRI is, however, impaired by several potential sources of error, as summarized in Refs. [17][18][19].…”
Section: Introductionmentioning
confidence: 99%